Effect of Litter Size on Milk Production of Does and Pre-weaning Growth of Kids in Crosses of Boer and Peranakan Ettawa (PE) Goats - Happy Poerwoto; Lalu Wirapribadi; Mohammad Ashari; Rr. Agustien Suhardiani (Jurnal Biologi Tropis, 2023)
Boerawa goats (Boer x PE Crossbred) which currently have been spread and farmed in various region of Indonesia need to be monitored their productivity and development continously. The aim of this experiment was to investigating the Doe's milk production and pre-weaning growth of the Boer x PE crossbred kids on different litter sizes. The experiment was conducted at MBB Goat Breeding Farm in Klebuh Village, Praya Tengah District, Central Lombok Regency. A total of 62 PE goat doe’s consisting of 15 single kidding and 47 twins kidding doe’s, each with their crossbred Boer x PE kids, were observed intensively by measuring their performance directly. Each doe’s was fed 250 g of concentrate mix (75%) and soybean meal (25%) and Ca & P minerals (0.5%) with chopped Elephant Grass basalt diet fed ad libitum. The results showed that the milk production of single kidding doe’s was lower than that of twin kidding doe’s (972 vs 814 ml/head/day). Birth weight and weaning weight of single kid were much higher (P<0.05) than twins. Birth weight (3.18 vs 2.45 kg), weaning weight (11.56 vs 8.33 kg), and daily weight gain (136.32 vs 88.63 kg), for (single kid vs. twin) respectively. The use of milk and the loss of body weight of the doe’s for the formation of every 1 g of body weight in single kid is relatively higher than those of twins.